The influence of atmospheric circulation on the formation of snow cover on the north eastern Siberia - N. K. Kononova (Лëд и снег, 2015)
Based on daily data of the five meteorological stations located in different parts of northeastern Siberia (Anadyr, Chokurdakh, Wrangell Island, Verkhoyansk, Markovo) the change of dates of formation, occurrence and maximum snow depth from year to year for the entire period of observation to 2008 is analyzed. The results are compared with long-term changes of the atmospheric circulation in the Northern Hemisphere and in a particular region (according to classification by B.L. Dzerdzeevskii, V.M. Kurganskaya and Z.M. Vitvitskaya). The differences in the fluctuations of selected indicators in circulation epochs are considered. The types of circulation, contribute to early or late formation of snow cover, as well as early or late it outright are identified. Macro-circulation processes which correspond with snowy or little snowy winters are defined. Time changing of maximum snow depth formation is considered. The change in frequency of extreme values of considered characteristics par circulation epochs and their relationship with macro-circulation processes, including possible tends, are analyzed. During recent years, in the Northeastern Siberia with sharp inter-annual fluctuations of atmosphere processes the later dates of setting and earlier dates of disappearance of snow cover dominate, which reduces the duration of snow cover, in comparison with long-term average. Maximum snow depth in all stations, except Anadyr, are above the average long-term value. There is a trend of increase the maximum snow depth, its duration, as well as its later formation, compare with the average, which indicates the increase in proportion of solid precipitation at the end of winter. These are facilitated by increasing of blocking atmospheric processes duration.